2013
DOI: 10.1111/bjd.12214
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety of ustekinumab in patients with moderate-to-severe psoriasis: final results from 5 years of follow-up

Abstract: SummaryBackground Long-term safety evaluations of biologics are needed to inform patient management decisions. Objectives To evaluate the safety of ustekinumab in patients with moderate-tosevere psoriasis treated for up to 5 years. Methods Safety data were pooled from four studies of ustekinumab for psoriasis. Rates of adverse events (AEs), serious AEs (SAEs) and AEs of interest [infections, nonmelanoma skin cancers (NMSCs), other malignancies and major adverse cardiovascular events (MACE)] per 100 patient-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
240
2
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(279 citation statements)
references
References 53 publications
(77 reference statements)
21
240
2
8
Order By: Relevance
“…Another 5-year study by Papp et al also showed that the rates of malignancies other than NMSC were comparable between the ustekinumab 45 mg (0.59 per 100 PY) and 90 mg (0.61 per 100 PY) groups without increasing trend. Overall, the incidence of malignancies other than NMSCs in ustekinumab-treated patients (0.60 per 100 PY) was consistent with that expected in the general U.S. population (range 0.54-0.72 per 100 PY) [17]. There is no evidence of a shift towards a pattern of malignancy indicative of severe immunosuppression.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Another 5-year study by Papp et al also showed that the rates of malignancies other than NMSC were comparable between the ustekinumab 45 mg (0.59 per 100 PY) and 90 mg (0.61 per 100 PY) groups without increasing trend. Overall, the incidence of malignancies other than NMSCs in ustekinumab-treated patients (0.60 per 100 PY) was consistent with that expected in the general U.S. population (range 0.54-0.72 per 100 PY) [17]. There is no evidence of a shift towards a pattern of malignancy indicative of severe immunosuppression.…”
Section: Introductionsupporting
confidence: 75%
“…In general, malignancy excluding NMSC was not significantly increased in patients receiving long-term ustekinumab therapy when compared with The National Cancer Institute's Surveillance Epidemiology and End Results (NCI SEER) database [15,17].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Overall, the rates of stroke and cardiovascular death were 0.03/100 PY and 0.07/100 PY, not statistically significant compared with placebo. There was no dose-dependent difference in the rate of overall risk of adverse events in patients who received 45 vs. 90 mg of UST [46]. The rate of other adverse events, including infections and malignancy were not statistically significant for either dose.…”
Section: Safety Of Ustekinumab In Treatment Of Psoriatic Arthritismentioning
confidence: 78%
“…An analysis of controlled clinical trials with ustekinumab showed an incidence of major cardiovascular events (MACE) of 0.44 per 100 patient years [82]. An analysis also including another IL12/23 antagonist (briakinumab) showed a significantly increased incidence of MACE vs. placebo [83].…”
Section: Cardiovascular Events Ustekinumabmentioning
confidence: 99%